2017
DOI: 10.1007/s12072-017-9801-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of histological features of idiopathic noncirrhotic portal hypertension in general population: a retrospective study of incidental liver biopsies

Abstract: The histologic features of INCPH are seen in incidental liver biopsies and fatty liver disease without portal hypertension. Ten percent of the biopsies show 5-6 features of INCPH without portal hypertension. Interpreting histologic features in the right clinical context is important for proper patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 28 publications
0
32
2
Order By: Relevance
“…We do not dispute the results of studies such as the Zuo et al report, which showed that histologic changes similar to those in INCPH can be observed in diseases other than INCPH [11]. However, it is not yet clear whether these similar pathologic changes found under INCPH and non-INCPH conditions are actually the same or not.…”
contrasting
confidence: 56%
See 3 more Smart Citations
“…We do not dispute the results of studies such as the Zuo et al report, which showed that histologic changes similar to those in INCPH can be observed in diseases other than INCPH [11]. However, it is not yet clear whether these similar pathologic changes found under INCPH and non-INCPH conditions are actually the same or not.…”
contrasting
confidence: 56%
“…On the other hand, histologic findings similar to those in INCPH have been reported in non-INCPH cases [11][12][13][14]. Zuo et al recently investigated fatty liver histopathologically and reported some interesting findings [11].…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…The gross pathology of IPH can be subcapsular parenchymal atrophy and nodular and thrombosis of the portal vein branches . Portal fibrosis, incomplete septa, and nodular regenerative hyperplasia (NRH) are typical histopathological features, along with occlusion of small portal vein, thickening of the portal vein wall, shunt vessel herniation into the liver parenchyma, sinusoidal dilatation, and phlebosclerosis …”
Section: Introductionmentioning
confidence: 99%